2021
DOI: 10.1002/fut.22269
|View full text |Cite
|
Sign up to set email alerts
|

Financialization, common stochastic trends, and commodity prices

Abstract: Commodity financialization has been a subject of discussion since the 2008 financial crisis. It is estimated that between 2003 and 2008, index investorsʼ positions increased from $13 billion to $317 billion. Surprisingly, most studies, predominantly based on Granger-causality testing, find no relationship between financialization and commodity prices. We examine the effects of shocks to the common stochastic trends in the index positions, the spot and futures prices of Chicago corn and soybeans, WTI crude oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…A plausible motivation for this interest is the need for accurately measure the volatility of energy futures prices. In fact, this variable plays a key role in the price connection between spot and futures markets—see, for example, Silvapulle and Moosa (1999), Lin and Tamvakis (2001), Hammoudeh et al (2003), Hammoudeh and Li (2004), Huang et al (2009), and Balcilar et al (2015)—on the linkage with economic and financial variables—as documented by Maréchal (2021), Prokopczuk et al (2021), Kupabado and Kaehler (2021), and Xu and Wang (2021)—and on risk management problems—see, for instance, Sadorsky (2006), Aloui and Mabrouk (2010), Yin et al (2021), and Ammann et al (2022). The time‐varying dynamics and contagion in commodity futures are explained in detail in Mehlitz and Auer (2021) and Gong, Jin et al (2022), respectively.…”
Section: Introductionmentioning
confidence: 94%
“…A plausible motivation for this interest is the need for accurately measure the volatility of energy futures prices. In fact, this variable plays a key role in the price connection between spot and futures markets—see, for example, Silvapulle and Moosa (1999), Lin and Tamvakis (2001), Hammoudeh et al (2003), Hammoudeh and Li (2004), Huang et al (2009), and Balcilar et al (2015)—on the linkage with economic and financial variables—as documented by Maréchal (2021), Prokopczuk et al (2021), Kupabado and Kaehler (2021), and Xu and Wang (2021)—and on risk management problems—see, for instance, Sadorsky (2006), Aloui and Mabrouk (2010), Yin et al (2021), and Ammann et al (2022). The time‐varying dynamics and contagion in commodity futures are explained in detail in Mehlitz and Auer (2021) and Gong, Jin et al (2022), respectively.…”
Section: Introductionmentioning
confidence: 94%
“…On the basis of previous studies of Tang and Xiong (2012), Henderson et al (2015), Basak and Pavlova (2016), and Kupabado and Kaehler (2021), our basic tenet is that because commodities became another asset class for portfolio inclusion, there are significant linkages between financial and commodity markets that allow the transmission of financial information and economic activity on commodity prices and ultimately on CY. The magnitude and significance of these effects will be analyzed through an econometric model with soybeans CY being the only dependent variable.…”
Section: Modeling Considerationsmentioning
confidence: 99%
“…For example, Basak and Pavlova (2016) reframed the supply of storage equation introducing relevant financial variables and concluded that financialization directly affects not only commodity futures prices but spot prices as well. Furthermore, Kupabado and Kaehler (2021) applied a structural vector error correction model and provided empirical evidence that financialization affects crude oil, natural gas, corn and soybeans futures, and spot prices in the short and long run.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations